Effect of casting temperature on dimensional accuracy in gravity casting - Mohd Shariman, Razali (2009)
In casting process the dimension of the final products is not accurate compared to the dimension of master pattern. This study is conducted to investigate the effect of casting temperature to the dimensional accuracy of the final products. In this study, wax holder is produced using gravity casting. The objective of this study is to investigate the effect of casting temperature on dimensional accuracy on the final product using gravity casting. Also, to find optimum melting temperature of paraffin wax in terms of dimensional accuracy of the final product compare with master pattern. In this process, three different setting of melting temperature are applied, which are 47°C, 55°C and 64°C. The dimension of final product is measured using vernier calipers. All the data are plotted as bar graph. From the graph, it showed that melting temperature 55°C have the best dimensional accuracy and low percentage of error compared with other melting temperature.